VISUAL METAPHORS AND SELF-DISCOVERY IN NIGHT AT THE MUSEUM - Rafadiena, Allida Elvia; EF, Abd. Hannan; Sudarisman, Yoga (Universitas Lambung Mangkurat, 2026)
Abstract: This study aims to describe how visual metaphors create the theme of self-discovery in Night at the Museum through the use of film as a visual narrative, and outline how various film techniques, such as imagery, movement, and space, are employed within the film to create these meanings, rather than relying solely on dialogue. This qualitative descriptive study investigates the use of mise en scène, space, movement, and objects in the creation of meaning through an analysis of selected scenes within the film using theories of cognitive metaphor. Findings from the study show that although comedy films provide viewers with entertainment, they also offer a rich source of material for analyzing narrative meaning and support Cognitive Metaphor Theory as an effective approach to analyzing mainstream films. Specifically, visual metaphors such as spatial transitions, movement between spaces, and symbolic interactions map the protagonist’s journey from uncertainty to self-awareness. Overall, this study adds to the existing literature regarding the use of visual metaphors to produce complex narrative meanings in mainstream film.Keywords: visual metaphor, self-discovery, film narrative, Night at the Museum, cinematic meaning